School Bullying Victimization and Associated Factors Among School-Aged Adolescents in China - Meng, Yanyuan (Journal of interpersonal violence, 2023)
There has been a significant amount of research on correlates of bullying victimization, but most prior studies are descriptive and do not distinguish between different types of bullying. The current study used a case-control study design to explore factors related to different types of bullying victimization, including physical, relational, verbal, sexual, property, and poly-bullying victimization. This study was conducted in a southern city in China, including 3054 cases who self-reported being victims of school bullying and 3054 controls who reported not being involved in any school bullying in the past 12 months. Each victim case was matched with a control on gender, school, and grade level. Univariate logistic analyses and multivariate conditional logistic regression analyses were used to identify factors associated with being a victim of school bullying. Results suggest physical bullying victimization was only associated with a family-level characteristic (parenting style) while the other four types of bullying victimization (relational, verbal, sexual, and property bullying) and poly-bullying victimization were associated with multiple social domain variables at individual, family, and school levels. Findings from this study provide evidence of factors for different types of bullying victimization and have implications for potential measures to prevent bullying. Measures from multiple social domains, including individual, family and school (e.g., developing healthy behaviors, improving social skills, positive parent-child interactions, building trust between teachers and peers, and forming strong friendships), should be considered in order to effectively prevent adolescent victimization from bullying.